Alumina grafted SBA-15 sustainable bifunctional catalysts for direct cross-coupling of benzylic alcohols to diarylmethanes. Issue 8 (3rd April 2020) - Rajendran, Chandran; Satishkumar, Govindaswamy; Lang, Charlotte; Gaigneaux, Eric M.
Abstract : AlSBA-15 catalysts possessing Brønsted acid and Lewis acid–base bifunctionalities catalyze the direct arylation of benzyl alcohols to diarylmethanes with an 85% product yield through C–O bond activation. Abstract : AlSBA-15 catalysts possessing Brønsted acid and Lewis acid–base bifunctionalities catalyze the direct arylation of benzyl alcohols to diarylmethanes with an 85% product yield through C–O bond activation. 2 and 4wt%AlSBA-15 catalysts have been synthesised by adopting a simple and efficient post-synthetic metal implantation route. The synthesised catalysts were characterized using XRD, N2 adsorption and desorption, 27 Al MAS NMR, XPS, HR-TEM, NH3 and CO2 -temperature-programmed desorption (TPD) and pyridine-transmission-FTIR spectroscopy techniques to confirm the existence of Brønsted acid and Lewis acid–base bifunctionalities. Through various control experiments, it is verified that Brønsted acid sites activate the benzyl alcohol and Lewis base sites interact with phenylboronic acid concurrently to accomplish the coupling reaction. In the recyclability study, 4wt%AlSBA-15 preserves its activity and stability up to 5 cycles. The 4wt%AlSBA-15 catalyst unlike homogeneous catalysts does not require additives, long reaction time and expensive metals.